AB0742 Intravenous Loading and Subcutaneous Maintenance with Secukinumab Provides Sustained Improvement in Multiple Measures of Disease Activity in Subjects with Active Ankylosing Spondylitis: 52-Week Data From the Randomized, Double-Blind, Placebo-Controlled, Phase 3 Measure 1 Study. (9th June 2015) - Wei, J. C.-C.; Baeten, D.L.; Geusens, P.; Porter, B.; Martin, R.; Richards, H.
Abstract : Background: Multiple methods of assessing disease activity in ankylosing spondylitis (AS) exist. We report the effect of secukinumab, a human anti–interleukin-17A monoclonal antibody, on disease activity in the phase 3 study, MEASURE 1 (NCT01358175 ). Objectives: To evaluate the short- (16 weeks [wks]) and long-term (52 wks) efficacy of intravenous (i.v.) loading and subcutaneous (s.c.) maintenance dosing of secukinumab on multiple disease activity endpoints. Methods: 371 adults with active AS were randomized to receive i.v. secukinumab 10 mg/kg (Wk 0, 2, 4) followed by s.c. secukinumab 75 mg every 4 weeks (10 IV→75 SC), i.v. secukinumab 10 mg/kg (Wk 0, 2, 4) followed by s.c. secukinumab 150 mg every 4 weeks (10 IV→150 SC), or placebo (PBO) on the same i.v. and s.c. dosing schedule. PBO subjects were re-randomized to secukinumab 75 mg or 150 mg s.c. based on Assessment of Spondyloarthritis International Society (ASAS) 20 response at Wk 16, with non-responders switched at Wk 16 and responders at Wk 24. Measures of disease activity included Ankylosing Spondylitis Disease Activity Score (ASDAS)-C-reactive protein (ASDAS-CRP), ASDAS-erythrocyte sedimentation rate (ASDAS-ESR), and Bath Ankylosing Spondylitis Disease Activity Index (BASDAI). The effect of secukinumab on individual components of the ASAS response criteria are also reported: patient's global assessment of disease activity and total spinal pain, both assessed on a visual analogue scale (VAS), Bath Ankylosing Spondylitis Functional Index (BASFI), and spinal inflammation based on BASDAI questions 5 and 6. Results: 84.8% and 89.5% of subjects in the secukinumab 10 IV→150 SC and 10 IV→75 SC arms, respectively, completed 52 wks of treatment. Secukinumab improved ASDAS-CRP, ASDAS-ESR, patient assessments of disease activity and pain, BASFI and BASDAI at Wk 16 vs PBO (Table ). At Wk 16 a higher proportion of subjects receiving secukinumab 10 IV→150 SC (58.4%) and 10 IV→75 SC (50.0%) achieved a clinically important change (decrease of ≥1.1) compared with PBO (16.4%) in ASDAS-CRP. Similarly, a higher proportion of subjects receiving secukinumab 10 IV→150 SC (56.0%) and 10 IV→75 SC (51.6%) achieved a clinically important change compared with PBO (14.8%) in ASDAS-ESR at Wk 16. Between 24% and 31% of secukinumab-treated subjects in either treatment arm achieved a major improvement (decrease of ≥2.0) in ASDAS-CRP or ASDAS-ESR at Wk 16 compared with 2% in the PBO arm. Due to the i.v. loading regimen utilized in both secukinumab arms, drug exposure levels were similar in the two groups through Wk 24. Improvements with secukinumab were sustained through 52 wks (Table ). Conclusions: Secukinumab rapidly reduces disease activity in subjects with active AS, with at least 50% of subjects achieving a clinically important change in ASDAS-CRP and ASDAS-ESR at Wk 16. These improvements were sustained over 52 wks. Acknowledgements: Medical writing support was provided by Rachel Mason at Seren Communications (Tytherington, UK), and was funded by Novartis. Disclosure of Interest: J. Wei Grant/research support from: BMS, Janssen, Pfizer, Sanofi-Aventis, and Novartis, Consultant for: Pfizer, Celgene, Chugai, UCB Pharma, and TSH Taiwan, Speakers bureau: Abbott, BMS, Chugai, Eisai, Janssen, and Pfizer, D. Baeten Grant/research support from: Boehringer-Ingelheim, Janssen, MSD, Novartis, and Pfizer, Consultant for: AbbVie, Boehringer-Ingelheim, BMS, Eli Lilly, Janssen, MSD, Novartis, Pfizer, Roche, and UCB, P. Geusens Grant/research support from: Pfizer, Abbott, Lilly, Amgen, MSD, Will, and Roche, Consultant for: Amgen, Speakers bureau: Amgen, Lilly, B. Porter Shareholder of: Novartis, Employee of: Novartis, R. Martin Employee of: Novartis, H. Richards Employee of: Novartis